P-106 Examination of an Alternative Definition for Clinical Remission in UC: Results from TOUCHSTONE, a Randomized, Double-Blind, Placebo-Controlled Trial of Ozanimod. (March 2016) - Sandborn, William; Feagan, Brian; D'Haens, Geert; Wolf, Doug; Vermeire, Severine; Hanauer, Stephen; Ghosh, Subrata; Smith, Heather; Cravets, Matthew; Frohna, Paul; Aranda, Richard; Gujrathi, Sheila; et al.
Abstract : Background: The Mayo score has been used to assess UC disease activity and to establish the efficacy of medications approved for the treatment of UC for over 2 decades. The definition of clinical remission used for approval of biologic agents since infliximab has been a Mayo score ⩽2 with no subscore >1, which is being scrutinized by the FDA due to its lack of formal validation and inclusion of the poorly-defined physician global assessment subscore (PGA). An alternative definition of clinical remission using the Mayo scoring system without the PGA, has been proposed that requires a rectal bleeding subscore (RBS) = 0, an endoscopy subscore (ES) of ⩽1 and a stool frequency subscore (SFS) ⩽1 with improvement ≥1. We have explored this alternative definition of remission in a post hoc analysis of the data from the TOUCHSTONE study. Methods: TOUCHSTONE was a randomized, double-blind, placebo-controlled trial designed to evaluate efficacy and safety of 0.5 mg (low dose, LD) and 1 mg (high dose, HD) ozanimod, an oral, selective sphingosine 1-phosphate (S1P) 1 and 5 receptor modulator, in comparison to placebo (PBO), in patients with moderate to severe UC. A total of 197 patients were randomized (1:1:1) and treated once daily with PBO (n = 65), LD (n = 65) or HD (n = 67). The patients who achieved clinical response at week 8 continued into the maintenance period (MP) with their original treatment for an additional 24 weeks. Using the data from TOUCHSTONE, we calculated clinical remission rates at weeks 8 and 32 applying the alternative definition of clinical remission, which excludes the PGA. Results: Of 197 patients in the IP, 103 (52.3%) continued in the MP and 91/103 (88.3%) completed. At week 8 using the original definition (Mayo score ⩽2 with no subscore >1) clinical remission occurred in 16.4% for HD ( P = 0.0482 versus PBO), 13.8% for LD ( P = 0.1422), and 6.2% for PBO while the alternate definition (RBS = 0, SFS ⩽1 with improvement ≥1, ES ⩽1), clinical remission occurred in 23.9%, HD ( P = 0.0154 versus PBO), 16.9%, LD ( P = 0.2099), and 9.2%, PBO. At week 32, using the original definition, clinical remission occurred in 20.9%, HD ( P = 0.0108 versus PBO), 26.2%, LD ( P = 0.0021), and 6.2%, PBO while using the alternative definition clinical remission occurred in 26.9%, HD ( P = 0.0025 versus PBO), 26.2%, LD ( P = 0.0053), and 7.7%, PBO. Conclusions: Using this alternative definition of clinical remission, a greater difference between HD and PBO was observed. An endpoint that excludes the PGA but maintains the other components of the Mayo score (RBS, ES, SFS) is able to demonstrate a treatment effect and could be one of the endpoints in clinical trials of UC. Further, the analysis confirms that patients with moderate to severe UC treated with ozanimod HD were more likely to both achieve and maintain clinical remission.